1979
DOI: 10.1002/ajh.2830060305
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific serum iron in thalassemia: Quantitation and chemical reactivity

Abstract: We reported earlier an abnormal iron population in the serum of patients with transfusional hemosiderosis secondary to thalassemia. The iron is not bound to transferrin, ferritin, or hemoglobin and is referred to as nonspecific iron. This publication reports studies of the chemical reactivity and nature of the nonspecific iron and the development and validation of a method for its quantitative analysis. The quantitation depends on the mobilization of this iron from nonspecific macromolecular binding sites by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 6 publications
0
32
0
Order By: Relevance
“…Iron in its free form i.e., in non-transferrin bound form is known to induce oxidation of biomolecules through Heber-Weiss and Fenton reactions by producing harmful hydroxyl radicals (4). This nontransferrin bound iron or free iron has been found in various disease conditions like hemochromatosis (5), thalasemias (6) and patients on supplemental iron therapy (7). In our previous work we also found such free iron in hemodialysis patients not on any supplemental iron (8).…”
Section: Introductionmentioning
confidence: 74%
“…Iron in its free form i.e., in non-transferrin bound form is known to induce oxidation of biomolecules through Heber-Weiss and Fenton reactions by producing harmful hydroxyl radicals (4). This nontransferrin bound iron or free iron has been found in various disease conditions like hemochromatosis (5), thalasemias (6) and patients on supplemental iron therapy (7). In our previous work we also found such free iron in hemodialysis patients not on any supplemental iron (8).…”
Section: Introductionmentioning
confidence: 74%
“…This is the reason why levels of NTBI in normal healthy individual do not exceed 1 lmol/L, and often undetectable by most of the methods [13]. In the iron overload scenarios like thalassemia; hemochromatosis and others iron gets a chance to exist in form which is not bond to Tf [2,[14][15][16][17][18]. Increased levels of NTBI in the above mentioned situations is easily explainable whereas it is difficult to give a convenient explanation for the raised levels of NTBI where Tf saturation is not high [18][19][20].…”
Section: Sources and Status Of Ntbi In Circulationmentioning
confidence: 99%
“…Endogenous source is more important factor as iron absorption is well regulated at the mucosal level. In hemolytic anemia, increased endogenous inflow of iron due to excess haemolysis and/or compensatory blood transfusion may cause higher saturation of Tf leading to existence of NTBI [2,14,15,21]. Lee et al [22] reported the existence of NTBI in diabetes mellitus.…”
Section: Sources and Status Of Ntbi In Circulationmentioning
confidence: 99%
“…The chemistry of the assay is extremely complex and is critically dependent on the source of bleomycin [4] (Fig. 3, formula 4).…”
Section: Bleomycin Assaymentioning
confidence: 99%